(3GdehVM aj JYdjd hLhg GdbQGAGJs - (3CMeO Hf YeGQ Hf CHj GdYHGS GdegOhj, CHh GdYHGS,J (B440 (3g` s ((3MdH s)
(3ChdgG (B:s
(3GeG HYO MeO Gddg HLejY eMGeOg, hTcQg Ydi Lejd YhGFOg hLRjd ahGFOg hbO SCdfj SGFdhf Gf Cedj Ydjge cJGHkG oeNJUQkG aj TQM hLhg GdbQGAGJ s
(3BNQgG (B:s
(3MeGdI GdWH (B: (3GdfUH Ydi GdPe , hGdQaY Ydi Cf GeQGI QaY HGdEHJOGA ced LejY GdOjhGf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs